Developing a User Interface Based on Prototyping of a Website Based Traffic Member Activity Recapitulation System - Nadhif Fadhillah, Moch; Budiman, Tedi (Jurnal Accounting Information System (AIMS), 2026)
The development of information technology has accelerated the need for administrative digitalization within law enforcement institutions, including traffic units. This study aims to design a web-based User Interface (UI) for the activity recap system that facilitates faster, more accurate, and integrated reporting by traffic officers. The research applies the Prototyping method, where system development is conducted iteratively with user involvement in each design evaluation stage. The main features include login, activity report input and verification, data recap, and user account management. The results indicate that the implementation of a responsive and intuitive UI design improves reporting efficiency, reduces data entry errors, and enhances transparency in internal reporting processes. The main contribution of this study lies in providing a user-centered UI design model for activity recapitulation systems in law enforcement environments, particularly for traffic police units, which can serve as a reference for similar digital transformation initiatives.